FENOMENA BAHASA GAUL SEBAGAI KOMUNIKASI GENERASI Z DI SEKOLAH MENENGAH ATAS NEGERI 1 BANDAR PERDAGANGAN - Harahap, Galang Rivaldy; Alfikri, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The popularity of the use of slang by generation z is very common, both in person and on social media. They are currently experiencing changes in the pronunciation and writing of Indonesian in accordance with the Big Indonesian Dictionary (KBBI) due to the emergence of a new style of language. So when using slang, it makes them feel more confident and considered contemporary. This study aims to find out the kinds of slang words, and to find out what factors influence the use of slang by Generation Z at State Senior High School 1 Bandar Perdagangan. This study used a qualitative descriptive method, with data collection techniques through interviews with 10 students in class 12 social sciences at State Senior High School 1 Bandar Perdagangan. As for the results of this study, it was concluded that the slang used by the z generation at State Senior High School 1 Bandar Perdagangan was only limited to a few forms of words according to needs, such as abbreviations, acronyms, word reversals, and the formation of new words. Meanwhile, the factors that influence the use of slang by generation z are advances in communication technology and the circumstances of the surrounding environment that encourage the development of slang.